2019
DOI: 10.1051/mmnp/2019003
|View full text |Cite
|
Sign up to set email alerts
|

Spatial externality and indeterminacy

Abstract: We study conditions for existence and uniqueness of solutions in some space-structured economic models with long-distance interactions between locations. The solution of these models satisfies non local equations, in which the interactions are modeled by convolution terms. Using properties of the spectrum location obtained by studying the characteristic equation, we derive conditions for the existence and uniqueness of the solution. This enables us to characterize the degree of indeterminacy of the system bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Last but not least, Fabbri [43] has specifically studied the impact of the shape of the domain on the optimal solution in this class of spatial growth models. In this issue, Augeraud-Véron and Ducrot [14] assess the impact of inter-regional disparities when the engine of growth is a learning by doing externality, modeled through non-local interactions. It is in particular shown that, depending on the type of interaction considered, local indeterminacy may occur.…”
Section: Spatial Growth Modelsmentioning
confidence: 99%
“…Last but not least, Fabbri [43] has specifically studied the impact of the shape of the domain on the optimal solution in this class of spatial growth models. In this issue, Augeraud-Véron and Ducrot [14] assess the impact of inter-regional disparities when the engine of growth is a learning by doing externality, modeled through non-local interactions. It is in particular shown that, depending on the type of interaction considered, local indeterminacy may occur.…”
Section: Spatial Growth Modelsmentioning
confidence: 99%